EFFECT OF LISINOPRIL AND ENALAPRIL ON QUALITY OF LIFE AND BLOOD PRESSURE DAILY PROFILE IN PATIENTS WITH STABLE ARTERIAL HYPERTENSION. - G. F. Andreeva; A. D. Deev; V. M. Gorbunov (Рациональная фармакотерапия в кардиологии)
Aim. To compare effect of long-term treatment with lisinopril and enalapril on quality of life (QL) and blood pressure (BP) daily profile in patients with stable arterial hypertension (AH). Material and methods. Analysis of three studies conducted in our center during last 4 years are presented (totally 86 patients were included). Protocol of studies was unified: after wash-out period ambulatory blood pressure monitoring (ABPM) and QL were assessed. Afterwards, patients were switched to active therapy with enalapril or lisinopril. After long-term treatment with these drugs QL and ABPM and QL were assessed again. Results. Both drugs decreased in systolic and diastolic BP, time index and didn't change heart rate and night BP dipping. With lisinopril treatment, significant improvement in physical condition, efficiency at work, psychological profile and capacity for social contacts was observed, while treatment with enalapril positively influenced only on physical condition and intensity of negative psychological profile in patients with stable AH. Conclusion. In patients with stable AH lisinopril had better influence on QL than enalapril. Therapy with both drugs lead to significant decrease in systolic and diastolic BP and didn't change heart rate and night BP dipping.